The Relationship between the Incidence of Diarrheal Disease and Environmental Health Sanitation in Sigi Regency, Sulawesi Tengah 2023 - Sri Anawati; Wa Ode Yanti (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Diarrhea is defined as the passage of stools more than three times a day, typically with loose or watery consistency, and may contain blood or mucus. It is a common condition and a significant public health problem worldwide (World Health Organization, 2019). In Indonesia, diarrhea remains a communicable disease that spreads easily and can lead to serious health consequences across all age groups. Objective: This study aims to describe the number of diarrhea cases affecting people of all ages in Central Sulawesi Province in 2023, based on data from the Central Sulawesi Provincial Health Profile. Methods: A descriptive case study design was employed. The study population consisted of patients of all ages diagnosed with diarrhea in Sigi Regency, Central Sulawesi Province, with consideration of environmental sanitation factors. Data on diarrhea cases were compiled from health center (Puskesmas) reports across 13 regencies/cities and presented in graphical form. Results: The analysis showed that the highest number of diarrhea cases for all ages occurred in Palu City, which also has the largest population in the province. Reports from health facilities indicated that Palu City accounted for 134.23% of the provincial case total. Across Central Sulawesi, the coverage of diarrhea case detection for all ages was 35.89% in 2021, decreased slightly to 32.98% in 2022, and increased to 40.57% in 2023. Conclusion: The fluctuating coverage of diarrhea case detection highlights the need for strengthened surveillance and improved environmental sanitation to reduce the disease burden. Keywords: Diarrheal disease, case detection, environmental sanitation, Central Sulawesi, Indonesia.